Volume 6: Ocean Engineering 2011
DOI: 10.1115/omae2011-50156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Favourable Free Fall Parameters for the AGaPaS Rescue Catamaran

Abstract: The joint research project “AGaPaS” (Autonomous Galileo-supported Rescue Vessel for Persons overboard) aims to significantly raise the chances of survival for people who have gone overboard. Its main objective is to develop a self activating, partially autonomously operating rescue system, able to search, find and rescue a drifting person [1]. A crucial part of the system is a remotely operated vessel, which is released by free fall from a mother ship. This type of launch offers a minimum response time but com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Kurowski et al [194] developed a satellite-guided SAR system, to be used in special ships and offshore platforms in case a person falls overboard. It consists of three main components: (1) A vest with an Automatic Identification System (AIS), worn by every crew member of a ship or offshore platform; (2) An autonomous twin-hull catamaran USV, referred to as the “rescue vessel” (described in detail in [195,196]); A satellite-aided control station. When a person falls overboard, the AIS vest activates upon contact with the water, and the SAR process starts.…”
Section: Usv Applications For Preventive Maintenance and Disaster mentioning
confidence: 99%
“…Kurowski et al [194] developed a satellite-guided SAR system, to be used in special ships and offshore platforms in case a person falls overboard. It consists of three main components: (1) A vest with an Automatic Identification System (AIS), worn by every crew member of a ship or offshore platform; (2) An autonomous twin-hull catamaran USV, referred to as the “rescue vessel” (described in detail in [195,196]); A satellite-aided control station. When a person falls overboard, the AIS vest activates upon contact with the water, and the SAR process starts.…”
Section: Usv Applications For Preventive Maintenance and Disaster mentioning
confidence: 99%
“…The tests have shown that the relative motion between the POB and the rescue vehicle impacted by the waves is small, and the person can be rescued even in rough seas (Figure 8). 16 In a second step, the entire search-and-rescue-system was validated. The focus lies on the autonomous approach to the POB by the rescue vessel, maintaining a safety distance to the POB, and maintaining the bearing to the POB automatically.…”
Section: System Testsmentioning
confidence: 99%
“…Considering the current development of numerical simulation technologies, it is found that most methods lead to more precise results in shorter computational times at ever increasing bandwidth in maritime applications. A few years ago, it was not conceivable that a standard personal computer would be able to calculate the resistance of a ship in some hours or that it would be possible to calculate complex dynamic processes, like the motion behavior of the freefall lifeboat AGaPaS 2 during a launch [1] or to investigate the efficiency of the Oil Skimming System SOS 3 [2] with CFD-simulations. In this paper, a technique well established for model tests at TUB, will be adapted to RANSE-methods.…”
Section: Introductionmentioning
confidence: 99%